Sosialisasi Penerapan Prinsip 3R (Reduse, Reuse and Recycle) dalam Menumbuhkan Karakter Peduli Lingkungan di Kampung Panggang Kota Serang - Nurfitria, Nadia; Nabila, Nazwa; Mardiyah, Sayyidatul (Jurnal PKM Manajemen Bisnis, 2024)
The accumulation of waste or throwing it carelessly into open areas will result in soil pollution which will also have an impact on groundwater channels. Waste must be handled from the source, namely from producers by applying the 3R principles of Reuse, Reduce and Recycle. Because without public awareness, the basic principles of an environmentally friendly lifestyle such as the 3Rs are difficult to implement and no matter how sophisticated the technology applied, the results will also never be optimal, which ultimately results in wasted budget funds. To provide knowledge and insight to the community about the importance of village cleanliness, hazardous waste management and prevention of infectious diseases, Community Service activities were carried out in socialization and training to the community of Kp. Panggang Serang City Banten. The goal is to foster the character of environmental care in Kp. Panggang. This activity was attended by 41 people and involved 2 students of the Islamic Broadcasting Communication Department, Faculty of Da'wah. The results of the implementation of this PKM activity are expected to add insight to the community of Kp. Panggang regarding environmental cleanliness, waste management and the application of the 3Rs. The results of this activity can be concluded that this PKM activity can add insight to facilitators in Kp. Panggang Serang City Banten, especially regarding waste management and to Foster Environmental Care Character is an initial effort to realize an eco-village through community empowerment starting with handling waste independently through the 3R method.